2009
DOI: 10.1074/jbc.m109.005793
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin Mediates β1-Adrenergic Receptor-Epidermal Growth Factor Receptor Interaction and Downstream Signaling

Abstract: ␤1-Adrenergic receptor (␤1AR) stimulation confers cardioprotection via ␤-arrestin-dependent transactivation of epidermal growth factor receptors (EGFRs), however, the precise mechanism for this salutary process is unknown. We tested the hypothesis that the ␤1AR and EGFR form a complex that differentially directs intracellular signaling pathways. ␤1AR stimulation and EGF ligand can each induce equivalent EGFR phosphorylation, internalization, and downstream activation of ERK1/2, but only EGF ligand causes trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 50 publications
12
104
3
Order By: Relevance
“…Although it has also been reported that memory reconsolidation requires protein synthesis but not PKA activation 24 h after training (36), the classical G protein/cAMP/PKA signaling pathway has been proposed to mediate the function of β-ARs in memory (6), and the signaling pathways leading to protein synthesis and memory restabilization are not clear. In this study, we showed that upon reactivation of a particular memory trace, β 1 -AR/β-arrestin2/ERK signaling and downstream effectors involved in protein translation, such as p90RSK and eIF4B (9,37), are activated in a distinct brain area. We found that this pathway, but not the conventional Gs protein-coupled PKA pathway, mediates memory reconsolidation, revealing an unexpected role of β-arrestin-biased signaling in brain physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has also been reported that memory reconsolidation requires protein synthesis but not PKA activation 24 h after training (36), the classical G protein/cAMP/PKA signaling pathway has been proposed to mediate the function of β-ARs in memory (6), and the signaling pathways leading to protein synthesis and memory restabilization are not clear. In this study, we showed that upon reactivation of a particular memory trace, β 1 -AR/β-arrestin2/ERK signaling and downstream effectors involved in protein translation, such as p90RSK and eIF4B (9,37), are activated in a distinct brain area. We found that this pathway, but not the conventional Gs protein-coupled PKA pathway, mediates memory reconsolidation, revealing an unexpected role of β-arrestin-biased signaling in brain physiology.…”
Section: Discussionmentioning
confidence: 99%
“…While activation of EGFR consistently enhances phosphorylation of cardiac ERK1/2 (Gotoh et al, 1992;Duquesnes et al, 2009;Tilley et al, 2009;Villa-Abrille et al, 2010;Akhtar et al, 2012), the importance of this MAPK to associated cardioprotection remains unclear. A number of studies provide support for ERK1/2 involvement in cardioprotection, whereas others report no role for the kinase in preconditioning and adenosine responses (Hausenloy and Yellon, 2006) Further analysis of ERK1/2 involvement in EGFR mediated cardioprotection is needed.…”
Section: Erk1/2mentioning
confidence: 99%
“…We assessed DNA binding of transcription factors reported to have putative binding sites in the CCR2 promoter and/or to regulate CCR2 expression [AP-1 (11), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) (12), and nuclear factor of activated T cells (NFAT) (13)], as well as cAMP response element binding protein (CREB) as a positive control, because it is known to be regulated downstream of βAR but with minimal impact on CCR2 transcription (14)(15)(16). AP-1 (Fig.…”
Section: Specific Ablation Of Ccr2 Reduces Leukocyte Recruitment To Thementioning
confidence: 99%